Determinants of Neonatal Readmission in Healthy Term Infants: Results from a Nested Case–Control Study - Hensman, Angelita M.; Erickson-Owens, Debra A.; Sullivan, Mary C.; Quilliam, Brian J. (American Journal of Perinatology, 2020)
Objective The aim of this study was to estimate the incidence and identify the factors associated with neonatal readmission among healthy term infants.Study Design A nested case–control study with matching was conducted at a large level III perinatal hospital with approximately 8,700 deliveries each year. Each case infant (n = 130) was matched to two control infants (n = 260) on the case infant's date of birth (±7 days) and the mother's maternal age (<20 years, 20–29, 30–39, and >39 years). All infants were selected from a cohort of eligible term, healthy, in-state infants admitted to the newborn unit postdelivery from January 1, 2016 to May 8, 2017. Data were analyzed using hierarchical conditional logistic regression.Results The incidence of neonatal readmission was 2.2%, and all readmissions occurred within 8.6 days of birth. Earlier gestational age (37 weeks; odds ratio [OR]: 4.11, 95% confidence interval [CI]: 1.79–9.45; 38 weeks OR: 1.29, CI 0.60–2.75; [ref] 39 weeks), jaundice on day two of life (OR: 2.45; CI: 1.40–4.30), maternal group B streptococcus chemoprophylaxis (OR: 2.55; CI: 1.23–5.28 [Ref N/A]) were associated with readmission. Delivery by cesarean section (OR: 0.31, CI: 0.12–0.79) and each milliliter of formula [first three days] (OR: 0.96; CI: 0.993–0.999) were protective.Conclusion Neonatal readmission in healthy term infants may potentially be reduced with identification of modifiable determinants of readmission prior to discharge. Policies to capture the true incidence of neonatal readmissions should include admissions to hospitals other than the birth hospital.
Keywords: epidemiology; breastfeeding; neonatal readmission; infant; newborn; nested case–control study; jaundice